Do patients of integrative anthroposophic pediatric inpatient departments differ? Comparative analysis to all pediatric inpatients in Germany considering demographic and clinical characteristics - Katharina Fetz; Thomas Ostermann; Melanie Schwermer; Sebastian Appelbaum; Jan Vagedes; Tycho Jan Zuzak; Alfred Längler (BMC, 2019)
Abstract Background Integrative medicine (IM) is a patient-centered, evidence-based, therapeutic paradigm which combines conventional and complementary approaches. The use of IM in pediatrics has increased in the past two decades and parents' demand for it is growing. An IM whole systems approach is anthroposophic medicine. Considering the growing demand for integrative approaches in children, it is relevant from a public health perspective to find out which kind of children use IM in Germany and whether they differ from the entirety of pediatric inpatients in Germany. Moreover, it would be interesting to known, whether these patients are willing to travel a longer distance to gain integrative treatment. Methods The present study investigates the standard ward documentation datasets of 29,956 patients of all German integrative anthroposophic pediatric inpatient wards from 2005 to 2016 and compares them systematically to collect data of the entirety of all pediatric inpatient wards in Germany. Apart from patients' age and gender, and the ICD-10 admission diagnoses, the geographical catchment area of the hospitals were analyzed. Results Sociodemographic characteristics of pediatric inpatients in the integrative anthroposophic departments (IAH) did not differ from the entirety of all pediatric inpatients. Regarding clinical characteristics, higher frequencies were found for endocrine, nutritional and metabolic diseases (IAH: 7.24% vs. 2.98%); mental, behavioral, and neurodevelopmental disorders (IAH: 9.83% vs. 3.78%) and nervous diseases (IAH: 8.82% vs. 5.16%) and lower frequencies for general pediatric diseases such as respiratory diseases (IAH: 17.06% vs. 19.83%), digestive diseases (IAH: 3.90% vs. 6.25%), and infectious and parasitic diseases (IAH: 12.88% vs. 14.82%) in comparison to the entirety of all pediatric inpatients in Germany. The IAH showed a broad catchment area, with most patients being from former, Western federal republic of Germany. Large catchment areas (> 100 km) for the IAH are merely covered by severe and chronic diseases. Conclusion Pediatric inpatients of IAH do not differ from the entirety of pediatric inpatients in Germany regarding sociodemographic characteristics but show differences regarding clinical characteristics. Parents are willing to travel further distance to get specialized integrative anthroposophic medical care for children with severe and chronic diseases.